What Do Market-Access Subsidies Do? Experimental Evidence from Tunisia - Nadia Ali; Giacomo De Giorgi; Aminur Rahman; Eric Verhoogen (Institute of Labor Economics (IZA), 2025)
Many countries seek to promote exports by subsidizing market access, but evidence on such efforts has been mixed. We present the first randomized evaluation of a government financial-support program explicitly targeting exports, the Tasdir+ program in Tunisia. The program offered matching grants for fixed market-access costs but not variable costs. Tracking outcomes in administrative data, we find positive effects on exports on average. We find limited impacts on the number of destinations or exported products, which were stated policy targets. The finding that the fixed-cost subsidies expanded exports on the intensive margin but not the extensive margins of destinations or products stands in contrast to the predictions of several workhorse trade models.
Keywords: F14; O14; 330; export promotion; market access; intensive margin